Ethnobotany, phytochemistry, pharmacology, and toxicity of Centella asiatica (L.) Urban: A comprehensive review. (31st August 2021) - Biswas, Dew; Mandal, Sujata; Chatterjee Saha, Suchismita; Tudu, Champa Keeya; Nandy, Samapika; Batiha, Gaber El‐Saber; Shekhawat, Mahipal S.; Pandey, Devendra Kumar; Dey, Abhijit
Abstract : The well‐known medicinal plant Centella asiatica (L.) Urban is an Ayurvedic and traditional Chinese medicine used in the treatment of different health problems and as an edible vegetable in a regular diet. Ease of availability in the wide range of environmental conditions plus low‐cost cultivation process has made the plant popular in ethno‐medicinal healthcare systems. In the present review, phytochemical analysis of plant‐extract and pharmacological activities of bioactive‐compounds are discussed based upon the available reports to understand their therapeutic potentialities along with the mechanisms behind. The results exhibited that C. asiatica and its triterpenoids demonstrated an array of pharmacological effects and health benefits, some of which were confirmed in many preclinical and clinical studies. Those reports also provided considerable evidences in support of the principles of folk treatment in different countries. Increase and maintenance of the prospective plant secondary metabolites would provide an enriched resource of drug molecules. Development of suitable derivatives of the therapeutic compounds can give an assurance for getting more effective drug candidates with reduced side effects. The review also enumerates the application of advanced nanotechnology, toxicology, and clinical‐trial reports on the plant with notes on the shortcomings in the present research and future perspectives of using this medicinal plant.